Characterisation of the Behavioural Effects of a Thoracic Squeeze in Healthy Newborn Piglets - Holdsworth SE; Kells NJ; Chidgey KL; Vallée E; Ward N; Mellor DJ; Beausoleil NJ (MDPI (Basel, Switzerland), 2021)
A thoracic squeeze has been observed to cause both healthy and low vigour neonatal foals to enter a ‘less-responsive state’, characterised by loss of posture, eye closure and cessation of movement, from which they rapidly recover to express normal healthy behaviours when the squeeze is released. To date, there have been no systematic studies characterising the responses of healthy neonates of other mammalian species to a thoracic squeeze. We describe the responses of healthy newborn piglets (n = 17) to a standardised application of the thoracic squeeze and evaluate the effect of the method of squeeze application on the response. Neonatal piglets were squeezed around the chest with either a soft fabric rope as has been used in foals (n = 8) or a novel purpose-made inflation cuff (n = 9). Both methods were effective at inducing a less-responsive behavioural state in all piglets, with neural reflexes reduced or absent in over half of them. The inflation cuff appeared to induce the less-responsive state faster than the rope, and more piglets squeezed with the cuff remained in this state for the full 10-min squeeze. These findings suggest that the behavioural response of foals to thoracic squeezing can be generalised to neonates of other precocial mammalian species. This initial study provides a foundation for further research using the inflation cuff to explore mechanisms underlying the thoracic squeeze and ways in which it may be applied whilst performing husbandry procedures.
Keywords: cessation of movement; chest squeeze; loss of posture; low vigour; neonatal piglets; reflex responses; thoracic squeeze; tonic immobility